2016
DOI: 10.15244/pjoes/62344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Compaction and Tillage Practices on Carbon Dioxide Efflux in Northeast China: Evidence from an Incubation Study

Abstract: Limited information is available for how soil compaction affects carbon dioxide (CO 2 ) efflux under different tillage systems. To improve understanding of the effects of compaction and tillage on soil CO 2 efflux, an incubation study consisting of no tillage (NT), moldboard plow (MP), and ridge tillage (RT) was conducted to explore the relationships between CO 2 efflux and bulk density, as well as pore size distribution under different levels of bulk densities, and the thresholds of bulk density and the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Previous research has reported a substantial decrease in organic carbon mineralization with rising BD. This decline could be attributed to the increase in soil compaction, leading to reduced soil aeration and consequently inhibiting the decomposition of soil organic carbon by microorganisms [55,56], consistent with our research. Nevertheless, the effect of BD on carbon mineralization is largely reflected in soil aeration and its impact may vary under the combined influence of different soil textures and water conditions [57].…”
Section: Analysis Of Driving Factors Of Soil Organic Carbon Mineraliz...supporting
confidence: 90%
“…Previous research has reported a substantial decrease in organic carbon mineralization with rising BD. This decline could be attributed to the increase in soil compaction, leading to reduced soil aeration and consequently inhibiting the decomposition of soil organic carbon by microorganisms [55,56], consistent with our research. Nevertheless, the effect of BD on carbon mineralization is largely reflected in soil aeration and its impact may vary under the combined influence of different soil textures and water conditions [57].…”
Section: Analysis Of Driving Factors Of Soil Organic Carbon Mineraliz...supporting
confidence: 90%
“…This means that earthworm activity has no effect on the small macropores. The reason for this situation was the partial destruction of large macropores by soil disturbance, resulting in the formation of a greater volume of small macropores under MP (Chen et al, 2016). Kay and van den Bygaart (2002) found that shifts from conventional to conservation tillage usually led to a reduction in the volume of small macropores.…”
Section: Soil Macroporosity With and Without Earthworms Under Differementioning
confidence: 99%